Biofiltration of a styrene/acetone vapor mixture in two reactor types under conditions of styrene overloading - Zapotocky,Lubos (2014)
This aim of study was to compare the performance of a biofilter (BF) and trickle bed reactor (TBR) under increased styrene loading with a constant acetone load, 2 gc/m3/h. At styrene loading rates up to 30 gc/m3/h, the BF showed higher styrene removal than TBR. However, the BF efficiency started to drop beyond this threshold loading and could never reach steady state, whereas the TBR continued to yield a 50% styrene removal. The acetone removal remained constant (93-98%) in both the reactors at any styrene loading. Once the overloading was lifted, the BF recovered within 26 min, whereas the TBR efficiency bounced back only to 95%, gradually returning to complete removal only in 10 h.